Proceedings of the International Symposium on Social Sciences, Education, and Humanities (ISSEH 2018) 2019
DOI: 10.2991/isseh-18.2019.42
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Religious Obedience Against Religious Tolerance on Junior High-School Student

Abstract: West Java is the province with the most followers of Islam. Of the total population of 43 million, almost 42 million are Muslims. However, according to BMPT the most radical act of Islamic radicalism occurred in West Java. It is as if there is a relationship between Islam and radicalism. Tasikmalaya is known as the most populous Muslims in West Java, reaching 98.73%. The study aims to find the relationship between religiosity and religious tolerance in junior high-school students in the city of Tasikmalaya. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…The latest research show that intolerance among children and adolescents are worrying. SMP/MTs students were reported tolerant and they accounted for 59%, 41% were categorized intolerance with their low level of tolerance (Rizal & Rahmat, 2019). Other study reported that the religious tolerance scores of high school students are at a moderate level and low level (Firdaus & Rahmat, 2017).…”
Section: Introductionmentioning
confidence: 97%
“…The latest research show that intolerance among children and adolescents are worrying. SMP/MTs students were reported tolerant and they accounted for 59%, 41% were categorized intolerance with their low level of tolerance (Rizal & Rahmat, 2019). Other study reported that the religious tolerance scores of high school students are at a moderate level and low level (Firdaus & Rahmat, 2017).…”
Section: Introductionmentioning
confidence: 97%
“…The research results from SMP were interesting, as although the Muslim students in West Java were much more religious concerning theology and rituals than the Christians, they were intolerant. Hence, the Christian students were much more tolerant than Muslims but less religious, and no correlation was found between religiosity and tolerance (Rizal & Rahmat, 2019). Criticism of Religious Education in the United Kingdom builds exclusive diversity but fails to engender mutual understanding among adherents (Clayton & Stevens, 2018).…”
Section: How Is Islamic Religious Education (Pai) In Schools and Collmentioning
confidence: 96%
“…Other research results show that more than half of UPI and PTN-PTS students in West Java have an exclusive religious thinking style (Rahmat, 2012). In a 2016-2020 research, a larger part of the students stated that followers of religions outside of Islam were infidels and would go to hell, while Muslims were automatically believers and heavenly expert (Firdaus & Rahmat, 2016a;Rizal & Rahmat, 2019;Firdaus & Rahmat, 2020;. Then, only 15% of the 380 UPI and UNSIL students accepted the presence of minority Islamic schools, while 52% were neutral, and 33% rejected it (Rahmat & Firdaus, 2020b).…”
Section: Review Of Literaturementioning
confidence: 99%